Integrated Activity and Genetic Profiling of Secreted Peptidases in Cryptococcus neoformans Reveals an Aspartyl Peptidase Required for Low pH Survival and Virulence. - Starlynn C Clarke; Phillip A Dumesic; Christina M Homer; Anthony J O'Donoghue; Florencia La Greca; Lenka Pallova; Pavel Majer; Hiten D Madhani; Charles S Craik (PLoS Pathogens, 2016)
The opportunistic fungal pathogen Cryptococcus neoformans is a major cause of mortality in immunocompromised individuals, resulting in more than 600,000 deaths per year. Many human fungal pathogens secrete peptidases that influence virulence, but in most cases the substrate specificity and regulation of these enzymes remains poorly understood. The paucity of such information is a roadblock to our understanding of the biological functions of peptidases and whether or not these enzymes are viable therapeutic targets. We report here an unbiased analysis of secreted peptidase activity and specificity in C. neoformans using a mass spectrometry-based substrate profiling strategy and subsequent functional investigations. Our initial studies revealed that global peptidase activity and specificity are dramatically altered by environmental conditions. To uncover the substrate preferences of individual enzymes and interrogate their biological functions, we constructed and profiled a ten-member gene deletion collection of candidate secreted peptidases. Through this deletion approach, we characterized the substrate specificity of three peptidases within the context of the C. neoformans secretome, including an enzyme known to be important for fungal entry into the brain. We selected a previously uncharacterized peptidase, which we term Major aspartyl peptidase 1 (May1), for detailed study due to its substantial contribution to extracellular proteolytic activity. Based on the preference of May1 for proteolysis between hydrophobic amino acids, we screened a focused library of aspartyl peptidase inhibitors and identified four high-affinity antagonists. Finally, we tested may1Δ strains in a mouse model of C. neoformans infection and found that strains lacking this enzyme are significantly attenuated for virulence. Our study reveals the secreted peptidase activity and specificity of an important human fungal pathogen, identifies responsible enzymes through genetic tests of their function, and demonstrates how this information can guide the development of high affinity small molecule inhibitors.